2009
DOI: 10.1097/prs.0b013e3181956633
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Frontonasoethmoidal Encephalocele: The HULA Procedure

Abstract: The authors' outcomes demonstrated that the HULA technique was a safe and effective approach for the complete correction of frontonasoethmoidal encephalomeningoceles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…22 Neurological complications and congenital brain anomalies are uncommon in fMEC, 28,38 and a majority of affected children are mentally normal. 15 Some of our parents reported that their child's malformation did not grow at all with time, whereas others (as reported by other authors) noted that their child's malformation became progressively larger. 9,38 Some authors therefore recommend early surgical correction to minimize the pressure effect of the mass on facial growth.…”
Section: Pathogenesis and Natural Historymentioning
confidence: 48%
See 2 more Smart Citations
“…22 Neurological complications and congenital brain anomalies are uncommon in fMEC, 28,38 and a majority of affected children are mentally normal. 15 Some of our parents reported that their child's malformation did not grow at all with time, whereas others (as reported by other authors) noted that their child's malformation became progressively larger. 9,38 Some authors therefore recommend early surgical correction to minimize the pressure effect of the mass on facial growth.…”
Section: Pathogenesis and Natural Historymentioning
confidence: 48%
“…More refined classifications based on CT findings can also be used. 15,24 However, when CT is not readily available, we think that the anatomical classification of Suwanwela and Suwanwela, although less accurate, is more practical.…”
Section: Classification Of Fmecsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the rare opportunity for surgical correction of these cases within the equine field, a human neurosurgeon (Pittman, MD, University of Kentucky College of Medicine, Lexington, Kentucky) was consulted to help with the procedure. Common techniques were followed, including excision of the herniated sac with preservation of as much normal‐appearing brain tissue as possible, bony reconstruction, and an emphasis on a tight dural closure . It has been recommended that these cases be treated before full bone development so that the skull has time to develop .…”
Section: Discussionmentioning
confidence: 99%
“…Patient surveys were modified for this specific patient group based on a focus group interview survey of 10 Romberg patients and their parents. 8,13 Additionally, the survey had been validated for intrarater and interrater reliability. 14 Physician and patient outcome satisfaction was based on symmetry, volume, and overall appearance in both the perioperative and follow-up periods as a 5-point scale (0 through 4).…”
Section: Methodsmentioning
confidence: 99%